Does Company Size Contribute to the Influence of Internal Factors on Environmental Accounting - Putri Hastuti, Hikmah; Gunawan Siregar, Indra (Inovasi Analisis Data, 2024)
This study aims to explore the influence of tax aggressiveness, profitability, leverage, and independent board of commissioners on corporate social responsibility (CSR) disclosure, as well as moderation by company size. Through data analysis of 13 infrastructure companies on the Indonesia Stock Exchange during the 2019-2023 period, with a total of 52 observational data, this study used purposive sampling method. The results show that tax aggressiveness and company size have a significant influence on CSR disclosure, while profitability, leverage, and independent board of commissioners do not show a significant influence. However, firm size moderates the relationship between tax aggressiveness and CSR disclosure, suggesting that larger firms tend to be more transparent in CSR disclosure to maintain their reputation. The theoretical implication of this study is that it provides a deeper understanding of the factors that influence CSR disclosure and the importance of firm size in that regard. Practically, this study provides insights for companies and regulators to improve their transparency and social responsibility. The novelty of this study lies in the approach of using company size as a moderator in the relationship between internal factors and CSR disclosure, particularly in the context of the infrastructure sector in Indonesia.